Plasmodium falciparum replication factor C subunit 1 is involved in genotoxic stress response. (23rd October 2020) - Sheriff, Omar; Yaw, Aniweh; Lai, Soak Kuan; loo, hooi linn; Sze, Siu Kwan; Preiser, Peter Rainer
Abstract: About half the world's population is at risk of malaria, with Plasmodium falciparum malaria being responsible for the most malaria related deaths globally. Antimalarial drugs such as chloroquine and artemisinin are directed towards the proliferating intra‐erythrocytic stages of the parasite, which is responsible for all the clinical symptoms of the disease. These antimalarial drugs have been reported to function via multiple pathways, one of which induces DNA damage via the generation of free radicals and reactive oxygen species. An urgent need to understand the mechanistic details of drug response and resistance is highlighted by the decreasing clinical efficacy of the front line drug, Artemisinin. The replication factor C subunit 1 is an important component of the DNA replication machinery and DNA damage response mechanism. Here we show the translocation of PfRFC1 from an intranuclear localisation to the nuclear periphery, indicating an orchestrated progression of distinct patterns of replication in the developing parasites. PfRFC1 responds to genotoxic stress via elevated protein levels in soluble and chromatin bound fractions. Reduction of PfRFC1 protein levels upon treatment with antimalarials suggests an interplay of replication, apoptosis and DNA repair pathways leading to cell death. Additionally, mislocalisation of the endogenously tagged protein confirmed its essential role in parasites' replication and DNA repair. This study provides key insights into DNA replication, DNA damage response and cell death in P. falciparum .